2005
DOI: 10.1086/499429
|View full text |Cite
|
Sign up to set email alerts
|

Further Spectroscopic Observations of the CSL 1 Object

Abstract: CSL-1 is a peculiar object (R.A. 2000 = 12 h 23 m 30"5; δ 2000 = −12 • 38 ′ 57"0) which, for its photometric and spectroscopic properties, is possibly the first case of gravitational lensing by a cosmic string. In this paper we present additional evidences, based on medium-high resolution VLT + FORS1 observations, that the spectra of the two components of CSL-1 are identical within a confidence level higher than 98% and the velocity difference of the two components is consistent with zero. This result adds fur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Although cosmic string cannot occupy dominant fraction of the energy density of the universe, its non-negligible population is still allowed observationally [40,41]. In fact, Sazhin et al [42,43] reported that CSL-1, which is a double image of elliptical galaxies with angular separation 1.9 arcsec, could be the first case of the gravitational lensing by a cosmic string with Gµ ≈ 4 × 10 −7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although cosmic string cannot occupy dominant fraction of the energy density of the universe, its non-negligible population is still allowed observationally [40,41]. In fact, Sazhin et al [42,43] reported that CSL-1, which is a double image of elliptical galaxies with angular separation 1.9 arcsec, could be the first case of the gravitational lensing by a cosmic string with Gµ ≈ 4 × 10 −7 .…”
Section: Introductionmentioning
confidence: 99%
“…The other possible explanation, that of a rare chance alignment of two identical giant ellipticals at the same redshift seemed very unlikely due to a series of odd circumstances: the two ellipticals should have been relatively near, = 11 kpc, each other, and in spite of this, undistorted, with identical (within the errors) spectra, and residing in a relatively low density environment (no other galaxies could be detected in the same region). Even though at the end it was proved that, in spite of all odds, this was the case [23], the detailed study of this anomalous object allowed to investigate in some detail another aspect of the expected observational effects induced by cosmic strings [13,17,22,24].…”
mentioning
confidence: 99%
“…Initially, the object was considered to be a double image lensed by a cosmic string. In 2005 new spectra of CSL-1 were taken with the Very Large Telescope operated by the European Southern Observatory and these observations were consistent with gravitational lensing by a cosmic string [71]. However, further observations with the Hubble space telescope showed that CSL-1 is a pair of very peculiar interacting elliptical galaxies [72,73].…”
Section: Lensing With Cosmic Stringsmentioning
confidence: 94%